GASING Method Training to Enhance Self-Confidence and Motivation in Speaking English: A Study of Student Perceptions among Semester IV and VI Students at STKIP Abdi Wacana Wamena: Pengabdian - Laura S. Maitimu; Dwi Puspitosari; Friska Simatupang; Danius Asso; Adriana Sem; Mina M. Kio (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Speaking instruction in the English Education Study Program at STKIP Abdi Wacana Wamena still faces challenges related to students' self-confidence, which results in nervousness, fear of making mistakes, and embarrassment when speaking English. Therefore, this Community Service (PKM) activity aims to enhance students' engagement, self-confidence, and motivation in learning English speaking through the implementation of the GASING method. The activity involved 25 students. Observation results show that almost all students were actively engaged throughout the stages of the GASING method, demonstrated confidence while speaking, and showed high enthusiasm until the end of the learning session. Interview results reinforce these findings: the majority of students expressed positive perceptions, stating that the method made learning less monotonous and provided equal opportunities to speak, while also helping to reduce the fear of making mistakes. Nevertheless, a small number of students felt that the GASING method was more suitable for Mathematics instruction than for English. Overall, these findings indicate that the GASING method was generally well received and effective in improving students' engagement, self-confidence, and motivation to speak, although further adjustments are needed to better fit the context of language learning.